2020
DOI: 10.3390/biom10050774
|View full text |Cite
|
Sign up to set email alerts
|

Living in a Foster Home: The Single Subpolar Flagellum Fla1 of Rhodobacter sphaeroides

Abstract: Rhodobacter sphaeroides is an α-proteobacterium that has the particularity of having two functional flagellar systems used for swimming. Under the growth conditions commonly used in the laboratory, a single subpolar flagellum that traverses the cell membrane, is assembled on the surface. This flagellum has been named Fla1. Phylogenetic analyses have suggested that this flagellar genetic system was acquired from an ancient γ-proteobacterium. It has been shown that this flagellum has components homologous to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…The regulon that looks closest to other alpha proteobacterial flagellar regulons is not expressed under normal laboratory conditions, but the Dreyfus group found that when induced it results in a polar tuft of flagella () [32]. The single, random, swim-stop flagellum we see normally in the lab appears to be the result of horizontal gene transfer [33–35]. It has not been possible to express the two systems together and the conditions causing switching between the two has not been identified.…”
Section: Rhodobacter Sphaeroides and More Unexpected Results!mentioning
confidence: 99%
“…The regulon that looks closest to other alpha proteobacterial flagellar regulons is not expressed under normal laboratory conditions, but the Dreyfus group found that when induced it results in a polar tuft of flagella () [32]. The single, random, swim-stop flagellum we see normally in the lab appears to be the result of horizontal gene transfer [33–35]. It has not been possible to express the two systems together and the conditions causing switching between the two has not been identified.…”
Section: Rhodobacter Sphaeroides and More Unexpected Results!mentioning
confidence: 99%
“…While electron micrographs of the isolated motors look similar to the basic motors of enteric species, the Dreyfus laboratory has identified additional motor proteins, an H-ring plus FliL and MotF. These appear to sit in the periplasmic region of the motor close to the outer membrane L/P ring, but unlike related FliL proteins, they appears to interact with the stator and be essential for motility ( Figure 2C ; Suaste-Olmos et al, 2010 ; Ramirez-Cabrera et al, 2012 ; Camarena and Dreyfus, 2020 ). The basic flagellar motors of species such as E. coli have a series of rings in the cytoplasmic and outer membrane.…”
Section: Genomics and Structurementioning
confidence: 93%
“…All review articles provide both expert and non-expert readers with advances in understanding the structures and functions of the bacterial flagellum. They highlight the most recent observations and illustrate perspectives for future research [4][5][6][7][8][9][10][11][12][13].…”
mentioning
confidence: 85%
“…The scope of this Special Issue is to cover recent advances in our understanding of the structures and functions of the bacterial flagellar motor derived from different bacterial species. This Special Issue includes ten review articles [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and eleven original research papers [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] from well-known experts in the field.…”
mentioning
confidence: 99%